CONTROLLABILITY OF STOCHASTIC IMPULSIVE NEUTRAL INTEGRODIFFERENTIAL SYSTEMS WITH INFINITE DELAY - Sathya, R.; Balachandran, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
The paper is concerned with the controllability of stochastic impulsive neutral integrodifferential systems with infinite delay in an abstract space. Sufficient conditions for controllability are obtained by means of semigroup theory and Banach contraction principle. An example is provided to illustrate the theory.